x-(x+1)=6

Simple and best practice solution for x-(x+1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(x+1)=6 equation:


Simplifying
x + -1(x + 1) = 6

Reorder the terms:
x + -1(1 + x) = 6
x + (1 * -1 + x * -1) = 6
x + (-1 + -1x) = 6

Reorder the terms:
-1 + x + -1x = 6

Combine like terms: x + -1x = 0
-1 + 0 = 6
-1 = 6

Solving
-1 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3q-10q-11-5= | | -8x+76=-212 | | u^2-221u+12100=0 | | 2x+5=161 | | 1.1x-1.4=-1.4 | | 15f+5g+45= | | 28u^4w^4y^9+12u^8w^7= | | -13-6x=1-4x | | 5x+23=118 | | 525.00+5x=525.00 | | (27x^9)^-1/3 | | Y=-x^2+1x | | x-7x+3=21 | | n(2)(-5)=11 | | 3x+5+6x=51 | | u^2-221u+16900=0 | | -2y+y-7=2 | | 6x+3(4x+6)=108 | | (6x+36)=2x-5 | | -8+4s=-18 | | 9y^2-x^3=9 | | 4x+18y=-27 | | 160=8timesn | | 0.25=x^2+x | | -d^2+12d+6=0 | | V^2/-4w^4 | | (x-5)(x-4)-2=x(x-7) | | 3a-5a-3=3 | | 35x^6-210x^5+315x^4=0 | | 7m-46=-4m+9 | | 8x+4y+z=377 | | 360=2x+y+x+y-x |

Equations solver categories